MANIPULATIVE DISCOURSE IN GEORGE ORWEL’S ANIMAL FARM - Basuki, Edi Pujo; Authar, Nailul (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2019)
Animal Farm has been called George Orwell’s most ferocious propaganda (Voorhees, 1961 quoted in Jasim, M. H. and Aziz, Fatimah H). This novel is a satire referring to a communist regime persistently utilizing the kind of hypocritical propaganda merely for the purpose of keeping its totalitarian regime in power.. Animal Farm demonstrates more of such manipulative discourse, and this will be the focus of the study. The contribution of this study is that understanding manipulative discourse and its strategies gives a view of manipulative mechanism and thereby help people recognizing any hegemony form by those in power. The framework of the study applied Cognitive Pragmatics for Manipulative Discourse and Relevance Theory. The result of the study describes the characters that represent manipulative discourse as well as the types of the employed strategies (both global and local, both linguistic and non-linguistic ones). Manipulative discourses employed in the novel are produced or reproduced for two main general purposes. Firstly, the political discourses produced by Old Major is to convince all the animals of the necessity to fight against the human being for the freedom of the animals. The ideology exercised by the animals is anti-human ideology. Secondly, the manipulative discourses produced and reproduced by the pigs are to exercise their domination over the rest of the animals. The ideology of the pigs’ racism is exercised to gain more power, more privilege, and more access to the farm resources.